Influence of the Post‐Synthesis Annealing on Device Performance of PbS Quantum Dot Photoconductive Detectors. Issue 18 (11th July 2018) - Shi, Yuansheng; Hu, Jinming; Jiang, Yurong; Sulaman, Muhammad; Yang, Shengyi; Tang, Yi; Zou, Bingsuo
Abstract : Colloidal quantum dots (CQDs) are attractive materials for optoelectronic devices due to their low‐cost, facile processing and size‐dependent band‐gap tunability and quantum confinement effect. In particular, narrow band‐gap lead chalcogenide CQDs have been widely used in near infrared optoelectronics. Here, in this paper, the influence of post‐synthesis annealing treatment on the active layer of PbS CQDs in photoconductive detector Au/PbS(110 nm)/Au is investigated by increasing the annealing temperatures from 80 to 140 °C, and the maximum photo‐to‐dark current ratio K and the specific detectivity D * are enhanced up to 9.7 and 23.2 times than those of the as‐made device, respectively, after the PbS active layer is annealed at 120 °C. Experimental data show that the dramatic enhancement of the device performance is due to the mobility enhancement of charge carriers and the perfect morphology of the PbS film after its annealing. Further, the underneath mechanisms for the enhanced‐performance after annealing are discussed in details, showing the performance of "top‐film" device is higher than that of the "bottom‐film" device. Abstract : Influence of post‐synthesis annealing on PbS CQDs layer in photoconductive detector Au/PbS(110 nm)/Au is investigated by increasing the annealing temperatures from 80 to 140 °C, and the maximum specific detectivity is enhanced up to 23.2 times (under 0.11 mW cm −2 850 nm illumination @10 V) than that of the as‐made device after the PbS active layer is annealed at 120 °C.